Deteksi Gen nuc (nuclease) Bakteri Methicillin Resistant Staphylococcus aureus (MRSA) Pada Sampel Ulkus Diabetikum Metode PCR - Lestari, Ari Fajar; Suliati, Suliati; Anggraini, Anita Dwi (poltekkes kemenkes pontianak, 2025)
Diabetic ulcers represent a common chronic complication of diabetes mellitus (DM) and are frequently associated with infections caused by Staphylococcus aureus. Staphylococcus aureus possesses multiple virulence factors, including the nuc (nuclease) gene, which encodes a thermonuclease enzyme capable of degrading DNA and destroying phagocytes within the host. Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of S. aureus exhibiting resistance to methicillin and other beta-lactam antibiotics. This study used conventional PCR Methode to detect the presence of the nuc (nuclease) gene in MRSA isolates obtained from patients with diabetic ulcers. A descriptive quantitative study with a cross-sectional design was conducted on 30 diabetic ulcer samples collected from Rumah Rawat Luka Surabaya between April and May 2025. Phenotypic identification and antibiotic susceptibility testing were performed, followed by molecular detection of the nuc (nuclease) gene using the conventional PCR method, generating an amplicon of 279 bp. The findings revealed that 19 of the 30 diabetic ulcer swab samples were phenotypically identified as Staphylococcus aureus. Antibiotic susceptibility testing indicated that 6 (31.6%) of these isolates were methicillin-resistant (MRSA). Among the 6 MRSA isolates, 3 (50%) tested positive for the nuc (nuclease) gene. This study emphasizes the application of molecular-based diagnostic methods such as PCR for the rapid detection of MRSA in diabetic ulcers, thereby supporting the selection of appropriate antibiotic therapy and improving the success of clinical management.